Influência da imagem corporal na autoestima de mulheres em tratamento do câncer de mama - Prates, Ana Carolina Lagos (2014)
Breast cancer is the most common disease in the female population, accounting for 22 % of new cases each year. In this sense, prevention is the best way to prevent disease. Are preventive measures for breast cancer: control of obesity, prátiva physical activity, not smoking, keeping the body in good nutritional status, avoid alcohol, do clinical examination, perform the breast self-exam and mammography often. Breast cancer causes doubts and distress in relation to body image, the maternal function, sexuality, conjugal love, life project and consideration of herself. Thus, body image impacts the self-esteem of these women in treatment. Objective: investigate the self-esteem of women with and without breast cancer, related to body image. Methods: A quantitative, case-control study in which 90 women with breast cancer were evaluated in the case group and 77 women without breast cancer in the control group. The study took place from March 2011 to February 2013. For data collection, the instrument of satisfaction with body image (ESIC) and the Rosenberg self-esteem questionnaire were used. SPSS version 16.0 - For statistical analysis, the Statistical Package for the Social Sciences software was used. Results: Compared to the women without breast cancer, those with breast cancer were more dissatisfied with body image related to appearance (p=0.001). Women undergoing neoadjuvant chemotherapy were more dissatisfied with their appearance compared to those with cancer who were not undergoing this treatment (p=0.019). Mastectomy also accounted for more dissatisfaction (p=0.001) concerning appearance compared to the women who were not submitted to this surgical procedure. On the other hand, women who underwent conservative surgery were more satisfied with their body appearance (p<0.001) in comparison to those submitted to other treatments. The perception of body image in relation to appearance was not affected in women submitted to breast reconstruction. Conclusion: Women with breast cancer were more dissatisfied with their body image compared to those without breast cancer, particularly following mastectomy or during chemotherapy. Self-esteem was found to be negatively affected in patients who were dissatisfied with their body image.